Large Nabothian Cyst: A Rare Cause of Nulliparous Prolapse. (13th June 2012) - Nigam, Aruna; Choudhary, Deepti; Raghunandan, Chitra
Abstract : Genital prolapse is commonly observed in postmenopausal and multiparous women, However, nulliparous women contribute to 2% of prevalence. We report a case of 21-year-old female who presented with a large nabothian cyst contributing to prolapse. This is the first case reported in the literature.